Feeding habits of Guiana dolphins, Sotalia guianensis, from south-eastern Brazil: New items and a knowledge review - Lopes, Xênia Moreira [UNESP]; Da Silva, Ednilson [UNESP]; Bassoi, Manuela; Dos Santos, Roberta Aguiar; De Oliveira Santos, Marcos César (Cambridge University Press (CUP), 2012)
This study presents new information on feeding habits of Guiana dolphins, Sotalia guianensis, in south-eastern Brazil, together with new regression equations to evaluate the weight and length of fish from otoliths, showing an overview on the knowledge about this species-diet in this area. Eighteen stomach contents had been analysed and compared to 180 samples collected in another eight feeding studies. The analysed specimens were either incidentally caught in gillnets used in coastal waters by the fleet based in the Cananéia main harbour (25°00âS 47°55âW), south of SÃ£o Paulo State, or found dead in inner waters of the Cananéia estuary between 2003 and 2009. Based on the index of relative importance analysis, the most important fish species were the banded croaker, Paralonchurus brasiliensis. Doryteuthis plei was the most representative cephalopod species. Stellifer rastrifer was the most important fish species observed in dolphins in inner estuarine waters and P. brasiliensis in recovered dolphins from coastal waters. Loliguncula brevis is the only cephalopod species reported from dolphins found in inner estuarine waters up to date. Doryteuthis plei was the most important cephalopod species observed in coastal dolphins. When considering other feeding studies, the most representative fish family in the diet of S. guianensis was Sciaenidae, which is mainly represented by demersal fishes. The main preys of S. guianensis are abundant in the studied areas, which may indicate an opportunistic feeding habit. The majority of them are not the most important target species by the commercial fishery in south-eastern Brazil. © 2012 Marine Biological Association of the United Kingdom.
Keywords: Brazil; Cetacea; feeding habits; Guiana dolphin; Sotalia guianensis; cephalopod; commercial species; demersal fish; dolphin; feeding behavior; gillnet; otolith; perciform; stomach content; Cananeia Estuary; Sao Paulo [Brazil]; Cephalopoda; Loligo; Paralonchurus brasiliensis; Pisces; Sciaenidae; Stellifer rastrifer